Pengembangan Komoditi Unggulan Dibidang Pertanian dan Potensi Wisata Goa - Nurmasita Madina; Ramadhani Chaniago; Agung K. Djibran; Rahmandani Lasamadi; Novianty; Risna Lasopo; Dinda Fira Dwi Sastra; Magfirawati Taiya; Yurita Tangahu; Yuyun Mira Safitri; Gita Wati; Sofyan Padiman; Sarwan Idan (Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2022)
The purpose of the Holistic Village Development and Empowerment Program (PHP2D) is to organize and promote the potential of cave tourism and the development of superior commodities such as soybeans, waxy vegetables in Lauwon Village, East Luwuk District, Banggai Regency, Central Sulawesi Province. The implementation method begins with outreach to village officials and target communities who are partners in the activity, then proceeds with structuring the outside of the cave and making a documentary film to promote the potential of cave tourism, training on making soybean coffee and wax vegetable sticks. The conclusions obtained from the implementation of this (PHP2D) are: 1) The community service activities in the form of PHP2D that have been carried out have been successful, the target partners are very enthusiastic in participating in every stage, from structuring village tourism potential to training activities. 2) The implementation of this program can produce outputs in the form of processed products that can be utilized by the community in adding to the family economy for each program participant and the entire village community.